Up the organization : - Townsend, Robert (Jossey-Bass, 2007)
Although it was first published more than thirty-five years ago, Up the Organization continues to top the lists of best business books by groups as diverse as the American Management Association, Strategy + Business (Booz Allen Hamilton), and The Wharton Center for Leadership and Change Management. 1-800-CEO-READ ranks Townsend’s bestseller first among eighty books that “every manager must read.”